2015
DOI: 10.1080/1350486x.2015.1050151
|View full text |Cite
|
Sign up to set email alerts
|

Pricing of Defaultable Bonds with Random Information Flow

Abstract: In the information-based approach to asset pricing the market filtration is modelled explicitly as a superposition of signals concerning relevant market factors and independent noise. The rate at which the signal is revealed to the market then determines the overall magnitude of asset volatility. By letting this information flow rate random, we obtain an elementary stochastic volatility model within the information-based approach. Such an extension is justified on account of the fact that in real markets infor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
2
1
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…In this way, impacts of a range of time-dependent informational strategies can be investigated. Of course, the information process { ξ t } is meant to represent the aggregate of the various information sources, and so is the variable σ (see [ 19 ] for how the aggregated information flow rate is related to that of the individual information source); whether it is time dependent or not. Thus, no one candidate has the access to control the overall value of σ .…”
Section: Discussionmentioning
confidence: 99%
“…In this way, impacts of a range of time-dependent informational strategies can be investigated. Of course, the information process { ξ t } is meant to represent the aggregate of the various information sources, and so is the variable σ (see [ 19 ] for how the aggregated information flow rate is related to that of the individual information source); whether it is time dependent or not. Thus, no one candidate has the access to control the overall value of σ .…”
Section: Discussionmentioning
confidence: 99%
“…In this way, the price process can be derived as an emergent phenomenon. For a deeper discussion of such an approach we refer the reader to [4], [5], [6], [8], [19] and [27]. This papers models default at predetermined times only, where the particularities of default were encoded in the a priory distribution of the random pay-off.…”
Section: Introductionmentioning
confidence: 99%
“…Brody et al suggested that the natural choice for β T is a standard Brownian bridge of length T . For a deeper discussion of this approach we refer the reader to [14], [15], [17], [21], [52] and [87].…”
Section: Introduction Introductionmentioning
confidence: 99%
“…In this way, price process can be derived as an emergent phenomenon. For a deeper discussion of such approach we refer the reader to [14], [15], [16], [17], [21], [52] and [87]. These papers models default at predetermined times only, where the particularities of default were encoded in the a priory distribution of the random pay-off.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation